Manure production, handling and use around Holetta Agricultural Research Center - Kumsa, T.; Madsen, J.O.; Tegegne, Azage (Ethiopian Society of Animal Production, 2004)
Fragmentation of farm lands and depletion of soil fertility are among the top most important limiting factors constraining subsistence farmers in maintaining sustainable crop production in the central highlands of Ethiopia. More than sixty and over a third of the total farm households in the country make their livings on less than a hectare and half a hectare, respectively. Due to the exorbitant price trends in the current markets for inorganic fertilizers, subsistent farmers tend to exploit their dependence on other options available to them like the use of organic fertilizer in maintaining soil fertility for sustainable cropping. This study undertaken as a survey work in a mixed crop/livestock farms around Holetta Research Centre in the central highlands of Ethiopia aimed at investigating the production, management and use of manure. The major sources of,manure in the area are cattle, though few farmers also keep sheep, goats, donkeys and horses. Farmers value manure from different livestock species differently and therefore house the species in separate shelters. Though variation in manure storage system exists, over 70 % of the surveyed farmers pile manure under open sun for about eight months before applying it to crop fields while only 11 % stored it in a pit. The storage of manure under open sun is argued to negatively affect its quality. Human and donkey power is the major means of manure transportation to crop fields and about 75 % of the labour for doing this job among the family members is provided by husband, wife and son. Ninety per cent of the respondents indicated that the crop field distance from homestead affects the possibility of manure transportation. Farmers Reported to use organic and inorganic fertilizers in mixture mainly to exploit the complementary effects and reduce fertilizer cost. Ninety eight per cent of the respondents indicated that they practice crop priority setting in cases of manure shortage, and about 38% and 24 % apply manure before and after field preparation, respectively.